2012
DOI: 10.1093/eurjhf/hfs063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of functional tricuspid regurgitation on heart failure and death in patients with functional mitral regurgitation and left ventricular dysfunction

Abstract: AimsThe prognostic role of tricuspid regurgitation (TR) associated with organic left-sided valvular heart disease is well known. However, no data are available regarding the prognostic value of functional TR (FTR) in patients with functional mitral regurgitation (FMR) and left ventricular (LV) dysfunction. The purpose of this study was to evaluate the prognostic role of FTR for occurrence of heart failure (HF) and mortality in patients with FMR. Methods and resultsWe enrolled 373 consecutive patients (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Functional TR in the absence of leaflet abnormalities frequently occurs in patients with heart failure by annulus dilatation and leaflet tethering1, 2, 3 and is associated with unfavorable outcomes 8, 9, 10, 11. Koelling et al demonstrated that severe functional TR was an independent predictor for all‐cause mortality in 1421 patients with LVEF <35% 9.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Functional TR in the absence of leaflet abnormalities frequently occurs in patients with heart failure by annulus dilatation and leaflet tethering1, 2, 3 and is associated with unfavorable outcomes 8, 9, 10, 11. Koelling et al demonstrated that severe functional TR was an independent predictor for all‐cause mortality in 1421 patients with LVEF <35% 9.…”
Section: Discussionmentioning
confidence: 99%
“…Koelling et al demonstrated that severe functional TR was an independent predictor for all‐cause mortality in 1421 patients with LVEF <35% 9. Agricola et al showed that moderate‐to‐severe functional TR was an independent determinant of overall mortality in 373 patients with heart failure during median follow‐up of 32 months 10. LVAD is an effective therapeutic option for end‐stage heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 To our knowledge, there are no published studies on whether the presence of PH in the non-ischemic heart with a reduced ejection fraction (EF) affects hemodynamic parameters and clinical outcome. We used cardiac catheterization with a micromanometer to investigate the relationship between PH and cardiac function, as well as the association between PH and clinical outcome, namely cardiac death or hospitalization for worsening HF, in ambulatory patients with DCM.…”
mentioning
confidence: 99%